AN EXACT ALGORITHM MINIMIZING THE MAKESPAN FOR THE TWO-MACHINE FLOWSHOP SCHEDULING UNDER RELEASE DATES AND BLOCKING CONSTRAINTS - Amdouni, Hajer; Jemmali, Mahdi; Mrad, Mehdi; Ladhari, Talel (International Journal of Industrial Engineering: Theory, Applications and Practice, 2022)
This paper describes the problem of two-machine permutation flowshop scheduling with release dates where blocking constraint is authorized. The objective is the minimization of the makespan. This problem is proved as an NP-hard problem. Four lower bounds were developed in this paper to test experimental results with different classes. An optimal solution is also proposed based on the mathematical formulation and solved using the Cplex program.